PENGELOLAAN DANA HIBAH MANDIRI ENTREPRENEUR CENTER UNTUK PENGEMBANGAN USAHA PARA ALUMNI - Rosyidah, Norma; Al Fiqri, Saifunuha (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2019)
This study aims to find out how the management of Mandiri Enterpreneur Center (MEC) grants in increasing the productivity of the business being run. In this study using a qualitative approach with descriptive analysis. Respondents in this study were 8 MEC alumni who received revolving grant funds from MEC in 2017 and 2018. The results of this study indicate that 62.5% of MEC alumni who received revolving funds were successful in starting their businesses. Then just 25% of MEC alumni who get revolving funds have succeeded in developing a business that is run. And only 12.5% of MEC alumni are unsuccessful in running their businesses. Based on these results it can be concluded that the revolving fund which became the MEC program has succeeded in increasing the productivity of alumni.